Maximizing anaerobic performance with repeated-sprint training in hypoxia: In search of an optimal altitude based on pulse oxygen saturation monitoring - Gutknecht, A. P.; Gonzalez-Figueres, M.; Brioche, T.; Maurelli, O.; Perrey, S.; Favier, F. B. (Frontiers in Physiology, 2022)
Purpose: Repeated-sprint training in hypoxia (RSH) leads to great improvements in anaerobic performance. However, there is no consensus about the optimal level of hypoxia that should be used during training to maximize subsequent performances. This study aimed to establish whether such an optimal altitude can be determined and whether pulse oxygen saturation during RSH is correlated with training-induced improvement in performance.